Síntese e caracterização de nanopartículas de ferritas de níquel e de colbalto preparadas pelo método sol-gel proteico - Gonçalves, Nizomar de Sousa (2011)
In this work we present the study of the synthesis of nanosized nickel and cobalt ferrites by sol-gel proteic method. This work revisited the method of X-ray powder diffraction analysis known as Williamson-Hall plotting. This method provides size-strain studies in nanoparticles samples. Nickel ferrites has presented particle sizes that increase when the calcination temperature increases. Nickel ferrites nanoparticles were characterized by Mössbauer spectroscopy. Sample calcined at 400°C has presented superparamagnetic properties and those calcined at higher temperatures behavior as magnetic materials. Cobalt ferrites nanoparticles were charcterized by X-ray powder diffraction, small angle X-ray scattering e magnetization. Cobalt ferrites has not presented superparamagnetic behavior. For the synthesis of cobalt ferrites some parameters that are important to the process control were studied: calcination temperature, calcination time, heat rate. We have shown the relation among those parameters and the particle size and properties control to the cobalt ferrite nanoparticles.